Assessing Performance of Cattle Dung and Waste Cooked Foods in Producing Biogas as Single Substrate and Mixed Substrates in Kampala Uganda - Mutesasira,, J; Mukasa-Tebandeke,, I.Z; Wasajja,, HZ; Nankinga,, R (Journal of New Developments in Chemistry, 2019)
Biogas is anaerobic degradation product formed from aqueous slurry of organic waste in a digester. It can be produced from cattle dung,(cd)chicken droppings, decaying leaves, kitchen waste foods(kwf), sewage sludge, slaughter house, goat, pig or sheep manure, Aqueous slurry of 200g/L of mixed or single substrate of cattle dung or/and kitchen waste evolved up to 400mL of biogas at ambient temperatures. The rate of gas evolution reached 5mL/day on the 15th day using 25% cd mixed slurry. The rates of degradation attained in the mixtures were 1.42ml/g for cd; 1.58mL/g for kwf; 1.78mL/g for 75% cd mixed substrate; 1.78mL/g for 50% cd mixed substrate; 1.92mL/g for 25% cd mixed substrate slurries. The comparative rate of biogas formation ranged from1.25 to 1.35 which was in agreement with the range published in literature of 0.8 to 5.5. Biogas can be synthesized efficiently at ambient temperature in Kampala as was done at mesophilic temperatures elsewhere. However, it may be necessary to attempt producing biogas at different pH and temperatures as well as using other substrates and inoculums.
Keywords: Substrate; co-generation; digester; cattle dung; bio-waste; kitchen waste